Review: An Enhancement of Road Scenes Captured Images Using HDCP and Color Discriptor - Kaur, Lakhveer; Kaur, Rajbhupinder (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
The visibility of images of outdoor road scenes will generally become degraded when captured during inclement weather conditions. Drivers often turn on the headlights of their vehicles and streetlights are often activated, resulting in localized light sources in images capturing road scenes in these conditions. Additionally, sandstorms are also weather events that are commonly encountered when driving in some regions. A novel and effective haze removal approach to remedy problems caused by localized light sources and color shifts, which thereby achieves superior restoration results for single hazy images. The Road image degradation can cause problems for intelligent transportation systems such as traveling vehicle data recorders and traffic surveillance systems, which must operate under a wide range of weather conditions. The objective of this work is to implement the Road Scenes Captured by Intelligent Transportation Systems using Hybrid technique. To enhance the images using different filters and enhancement techniques.